Effect of Plant Extracts Combinations on TNF-α, IL-6 and IL-10 Levels in Serum of Rats Exposed to Acute and Chronic Stress - Ilin Kandilarov; Petya Gardjeva; Maria Georgieva-Kotetarova; Hristina Zlatanova; Natalia Vilmosh; Ivanka Kostadinova; Mariana Katsarova; Kiril Atliev; Stela Dimitrova (Plants, 2023)
Oxydative stress, anxiety and depression are associated with changes in cytokine levels. Natural products, including individual and combined plant extracts, have the potential to be used in the treatment of neuropsychiatric disorders. The goal of this study is to investigate the effects of two combined plant extracts, rich in flavonoids, on the levels of the cytokines TNF-α, IL-6, and IL-10 in rats subjected to models of acute cold stress and chronic unpredictable stress. The study utilized common medicinal plants such as Valeriana officinalis, Melissa officinalis, Crataegus monogyna, Hypericum perforatum, and Serratula coronata, which were combined in two unique combinations—Antistress I and Antistress II. The compositions of the used extracts were determined by HPLC methods. Pro- and anti-inflammatory cytokines in rats’ serum were measured with Enzyme-linked immunosorbent assay. The results from the acute stress model revealed that the individual extract of Crataegus monogyna decreased levels of TNF-α, while Serratula coronata, Hypericum perforatum, and Valeriana officinalis effectively reduced IL-6 levels. Both combinations, Antistress I and Antistress II, were effective in reducing TNF-α and IL-6 levels, with Antistress II also increasing IL-10 levels. In the chronic stress model, Hypericum perforatum extract decreased the levels of the pro-inflammatory cytokines TNF-α and IL-6, whereas extracts of Serratula coronata and Valeriana officinalis only reduced TNF-α levels. The two combined extracts, Antistress I and Antistress II, decreased TNF-α and IL-6 levels, while Antistress I also reduced the levels of the anti-inflammatory cytokine IL-10. The combinations of plant extracts used in our experiment have not been previously studied or documented in the available literature. However, based on our own experimental results, we can draw the conclusion that the combinations exhibit a more pronounced effect in reducing cytokine levels compared to the individual plant extracts.